SELF- MANAGEMENT IN HYPERTENSION PATIENT - Dinda Ebti Safitri; Tien Aminah; Riki Ristanto; Alfunnafi Fahrul Rizzal; Bayu Budi Laksono (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2024)
Background Uncontrolled hypertension can cause complications of hypertension. The codition of increasing complications of hypertension is influenced by the lack of hypertensive self-management behavior. One of them is the lack of healthy living behaviors such as smoking, eating a high meaning of salt and lack of monitoring of blood pressure. The purpose of this study was to determine the picture of self-management of hypertension sufferers in Malang Regency. Method This research is a quantitative research with a descriptive research design. The population of this study was hypertension sufferers in Malang 40 people. The sampling technique used is purposive sampling. This research was conducted on June- July, 2023. Data collection instrument using HSMBQ questionnaire (Hypertension Self- Management Behavior Quetionnaire). Result The results showed that hypertension self-management behavior almost entirely (85%) had sufficient self-management. A small percentage (10%) have less self-management, and (5%) have good self-management. Based on the analysis of the question items, the results of self-management of people with low hypertension were obtained on indicators of self- integration, self-regulation, and blood pressure monitoring. Based on the results of this study, it is hoped that people with hypertension can apply hypertension self-management, it can also be an input and consideration to apply the correct self-management behavior in preventing complications and recurrences of hypertension